HERNIA INGUINALIS LATERAL - Jon Hadi; Abdul Raziq Jamil; Irsal Munandar (Nusantara Hasana Journal, 2025)
Lateral inguinal hernia, an indirect type of inguinal hernia, occurs due to a persistent processus vaginalis or weakness of the abdominal wall and is commonly found in males, requiring proper management to prevent complications. This paper is a literature review analyzing epidemiology, clinical presentation, diagnostic methods, and surgical management based on current scientific sources. The review shows that diagnosis is primarily established through clinical examination, with ultrasonography used as supportive imaging when needed, while surgical repair using open or laparoscopic techniques is effective with low recurrence rates, and laparoscopy offers faster recovery. It is concluded that lateral inguinal hernia requires early detection and operative intervention to prevent incarceration or strangulation, and that modern surgical techniques provide an excellent prognosis.